2022
DOI: 10.1007/s10456-021-09828-z
|View full text |Cite
|
Sign up to set email alerts
|

PHD2 deletion in endothelial or arterial smooth muscle cells reveals vascular cell type-specific responses in pulmonary hypertension and fibrosis

Abstract: Hypoxia plays an important regulatory role in the vasculature to adjust blood flow to meet metabolic requirements. At the level of gene transcription, the responses are mediated by hypoxia-inducible factor (HIF) the stability of which is controlled by the HIF prolyl 4-hydroxylase-2 (PHD2). In the lungs hypoxia results in vasoconstriction, however, the pathophysiological relevance of PHD2 in the major arterial cell types; endothelial cells (ECs) and arterial smooth muscle cells (aSMCs) in the adult vasculature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…To characterize the potential role of Angpt4 in the AH drainage and SC, we first investigated its expression in the iridocorneal angle. By crossing the genetic cell fate mapping mouse line Rosa26 mTmG with Angpt4 Cre mice, 23 , 38 we were able to visualize the cells that express or have expressed Cre recombinase under the Angpt4 promoter by Cre-mediated conversion of continuous tdTomato expression to membrane-targeted green fluorescence protein (GFP) expression. We observed that the Angpt4 -driven GFP signal started postnatally: at P5 (postnatal day 5) and P10, flat-mounted corneal limbus samples had only very few, faint GFP + cells, while at P13, their number and signal intensity were beginning to multiply ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the potential role of Angpt4 in the AH drainage and SC, we first investigated its expression in the iridocorneal angle. By crossing the genetic cell fate mapping mouse line Rosa26 mTmG with Angpt4 Cre mice, 23 , 38 we were able to visualize the cells that express or have expressed Cre recombinase under the Angpt4 promoter by Cre-mediated conversion of continuous tdTomato expression to membrane-targeted green fluorescence protein (GFP) expression. We observed that the Angpt4 -driven GFP signal started postnatally: at P5 (postnatal day 5) and P10, flat-mounted corneal limbus samples had only very few, faint GFP + cells, while at P13, their number and signal intensity were beginning to multiply ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Angpt4 Cre/+ ; Rosa26 mTmG/+ cell fate mapping and Angpt4 LacZ reporter mice have been introduced before. 23 , 38 …”
Section: Methodsmentioning
confidence: 99%
“…For instance, the aberrant proliferation of smooth muscle cells increased periarterial fibrosis and consequently promoted pulmonary hypertension. [ 29 , 30 ] Smooth muscle cells repression relieved pulmonary hypertension through fibrosis inhibition. [ 31 ] In a meniscus injury model, smooth muscle cells proliferated and migrated to the injury site to promote repair.…”
Section: Discussionmentioning
confidence: 99%
“…The associated significantly dysregulated genes included IGHV1-58, CWH43, IGHV1-54, IGKV4-63, IGHV1-75, and IGKV1-135 . Imbalanced angiogenesis and abnormal blood vessel function is a common pathological process in respiratory disorders, including idiopathic pulmonary fibrosis, pulmonary arterial hypertension, chronic obstructive pulmonary disease, hepatopulmonary syndrome, and cigarette associated lung injury ( Hanumegowda et al, 2012 ; Raevens et al, 2018 ; Eldridge and Wagner, 2019 ; Yang et al, 2021 ; Elamaa et al, 2022 ). Angiogenesis was also observed during the early to middle stages of RIPF.…”
Section: Discussionmentioning
confidence: 99%